Rationalising drug delivery using nanoparticles: a combined simulation and immunology study of GnRH adsorbed to silica nanoparticles. Issue 1 (December 2018) - Connell, David; Gebril, Ayman; Khan, Mohammad; Patwardhan, Siddharth; Kubiak-Ossowska, Karina; Ferro, Valerie; Mulheran, Paul
Abstract Silica nanoparticles (SiNPs) have been shown to have significant potential for drug delivery and as adjuvants for vaccines. We have simulated the adsorption of GnRH-I (gonadotrophin releasing hormone I) and a cysteine-tagged modification (cys-GnRH-I) to model silica surfaces, as well as its conjugation to the widely-used carrier protein bovine serum albumin (BSA). Our subsequent immunological studies revealed no significant antibody production was caused by the peptide-SiNP systems, indicating that the treatment was not effective. However, the testosterone response with the native peptide-SiNPs indicated a drug effect not found with cys-GnRH-I-SiNPs; this behaviour is explained by the specific orientation of the peptides at the silica surface found in the simulations. With the BSA systems, we found significant testosterone reduction, particularly for the BSA-native conjugates, and an antibody response that was notably higher with the SiNPs acting as an adjuvant; this behaviour again correlates well with the epitope presentation predicted by the simulations. The range of immunological and hormone response can therefore be interpreted and understood by the simulation results and the presentation of the peptides to solution, paving the way for the future rational design of drug delivery and vaccine systems guided by biomolecular simulation.